2021
DOI: 10.3389/fpsyg.2021.686414
|View full text |Cite
|
Sign up to set email alerts
|

Social-Ecological Predictors of Opioid Use Among Adolescents With Histories of Substance Use Disorders

Abstract: Adolescent opioid misuse is a public health crisis, particularly among clinical populations of youth with substance misuse histories. Given the negative and often lethal consequences associated with opioid misuse among adolescents, it is essential to identify the risk and protective factors underlying early opioid misuse to inform targeted prevention efforts. Understanding the role of parental risk and protective factors is particularly paramount during the developmental stage of adolescence. Using a social-ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 97 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…58 Risk factors for developing OUD in a vulnerable adolescent include perceived availability of opioids, antisocial traits, and parental history of substance misuse. 57,58 Navigating OUD is daunting, but there are effective evidence-based treatment options available including methadone, buprenorphine, and naltrexone. Unfortunately, a large systematic review found that adolescents are less likely to access these treatments than adults.…”
Section: Resultsmentioning
confidence: 99%
“…58 Risk factors for developing OUD in a vulnerable adolescent include perceived availability of opioids, antisocial traits, and parental history of substance misuse. 57,58 Navigating OUD is daunting, but there are effective evidence-based treatment options available including methadone, buprenorphine, and naltrexone. Unfortunately, a large systematic review found that adolescents are less likely to access these treatments than adults.…”
Section: Resultsmentioning
confidence: 99%
“…RLE have a unique lens through which they understand the complicated systems and interactions that people with substance use histories encounter while also having formal academic training in implementation science. From a lifespan perspective, the experiences of RLE may include interactions with multiple systems of care, such as child welfare, juvenile justice, educational settings, specialty treatment centers, aftercare settings, supportive housing, corrections, hospitals, and clinics ( Bronfenbrenner, 1979 ; Nargiso et al, 2015 ; Nichols et al, 2021 ). Lived interactions with these systems enhance collaborations with community partners and may advance the identification of potential barriers and elements of social and structural stigma that might otherwise go unnoticed ( Ahern et al, 2007 ; Morgan et al, 2015 ; van Boekel et al, 2013 ).…”
Section: Improving the Adoption And Implementation Of Evidence-based ...mentioning
confidence: 99%
“…Over 50% of adolescents who completed the Drug-Free America survey stated that it was easier to obtain these drugs from a medicine cabinet in their family's house than to receive illegal drugs from dealers [19]. Parents who are unaware of safe storage and disposal practice model unsafe behaviors in the home [20,21]. Coupled with youths' misunderstandings about opioids, it is critical to design novel interventions that are tailored to and target adolescents.…”
Section: Introductionmentioning
confidence: 99%